Calorespirometric feeding control enhances bioproduction from toxic feedstocks—Demonstration for biopolymer production out of methanol. Issue 10 (18th April 2016) - Rohde, Maria‐Teresa; Paufler, Sven; Harms, Hauke; Maskow, Thomas
ABSTRACT: The sustainable production of fuels and industrial bulk chemicals by microorganisms in biotechnological processes is promising but still facing various challenges. In particular, toxic substrates require an efficient process control strategy. Methanol, as an example, has the potential to become a major future feedstock due to its availability from fossil and renewable resources. However, besides being toxic, methanol is highly volatile. To optimize its dosage during microbial cultivations, an innovative, predictive process control strategy based on calorespirometry, i.e., simultaneous measurements of heat and CO2 emission rates, was developed. This rarely used technique allows an online‐estimation of growth parameters such as the specific growth rate and substrate consumption rate as well as a detection of shifts in microbial metabolism thus enabling an adapted feeding for different phases of growth. The calorespirometric control strategy is demonstrated exemplarily for growth of the methylotrophic bacterium Methylobacterium extorquens on methanol and compared to alternative control strategies. Applying the new approach, the methanol concentration could be maintained far below a critical limit, while increased growth rates of M. extorquens and higher final contents of the biopolymer polyhydroxybutyrate were obtained. Biotechnol. Bioeng. 2016;113: 2113–2121. © 2016 Wiley Periodicals, Inc. Abstract : A calorespirometric process control strategy for the conversion of toxic substrates into industry‐relevant chemicals was developed and demonstrated exemplarily for growth of the methylotroph Methylobacterium extorquens on methanol. Feeding control is based on biocalorimetry for an online estimation of growth parameters such as the specific growth rate and uses calorespirometric data to distinguish between different microbial growth phases. Applying this approach, cultures reached considerably higher growth rates and product yields on methanol compared to different control strategies.